Affective Information Processing in Self-Managing Teams: The Role of Emotional Intelligence - Paik, Yonjeong; Seo, Myeong Gu; Jin, Sirkwoo (Journal of Applied Behavioral Science, 2019)
Based on a multilevel data set collected from 599 individuals working in 102 self-managing teams, we examined the relationship between emotional intelligence (EI) and team member performance, focusing on the dimensions of teamwork and leadership performance. Furthermore, we explored the moderating role of team-level characteristics, such as noninformational diversity, size, and collective EI on the EI–performance relationship. As predicted, team members with higher EI were better at facilitating teamwork and playing the role of an informal leader than those with lower EI. The positive contribution of EI on team member performance was stronger for teams with greater diversity, larger sizes, and with lower average levels of team member EI. The study suggests that managers of self-managing teams should emphasize EI in their selection, training, and evaluation systems.
Keywords: affective information processing; emotional intelligence; self-managing teams; team diversity; team size